PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENGGUNAAN WEBSITE SEBAGAI MEDIA INFORMASI PADA POLSEK PORSEA KABUPATEN TOBA SAMOSIR - M Irfan Fahmi; Wan Mariatul Kifti; Nasrun Marpaung (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Use of the website at any institution or institution that uses the right technology as a medium to provide the latest information. Community Service Activities use information technology in the use of websites as information media to provide up-to-date and directly obtained information from police institutions for the community. With the existence of a website on the Porsea police station, it can improve the quality of Porsea police services against the Porsea community in receiving information, news about the Porsea area, and finding progress in increasing the entire Porsea police station that can be directly accessed by the Porsea community. The training method used is the indoor training method using the lecture method, discussion and question and answer and direct practice related to the use of the website. By applying the application in practice, it will increase knowledge about Porsea police in using applications to process and post news, information, and forms of service to Porsea police.